2018
DOI: 10.3389/fncir.2018.00103
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Constituents and Putative Interactions Within the Drosophila Ellipsoid Body Neuropil

Abstract: The central complex (CX) is a midline-situated collection of neuropil compartments in the arthropod central brain, implicated in higher-order processes such as goal-directed navigation. Here, we provide a systematic genetic-neuroanatomical analysis of the ellipsoid body (EB), a compartment which represents a major afferent portal of the Drosophila CX. The neuropil volume of the EB, along with its prominent input compartment, called the bulb, is subdivided into precisely tessellated domains, distinguishable bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
165
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(183 citation statements)
references
References 92 publications
18
165
0
Order By: Relevance
“…Both R2 and R4m ring neuron populations target the outer central domain of the EB, albeit following different trajectories (Fig. 6A,B) (Omoto et al, 2017(Omoto et al, , 2018. As with TuBu s micro-glomerular outputs, we found that only a subset of R2 neurons in the BUs were modulated by polarized light, with above-threshold PSI values typically in a medial cluster with a preferred angle of polarization (AoP) around 45° (Fig.…”
Section: R4m Ring Neurons Receive Polarization-tuned Responses From Tmentioning
confidence: 67%
See 1 more Smart Citation
“…Both R2 and R4m ring neuron populations target the outer central domain of the EB, albeit following different trajectories (Fig. 6A,B) (Omoto et al, 2017(Omoto et al, , 2018. As with TuBu s micro-glomerular outputs, we found that only a subset of R2 neurons in the BUs were modulated by polarized light, with above-threshold PSI values typically in a medial cluster with a preferred angle of polarization (AoP) around 45° (Fig.…”
Section: R4m Ring Neurons Receive Polarization-tuned Responses From Tmentioning
confidence: 67%
“…6A), where their arborizations have a circular form and are both dendritic and axonal ( Fig. 6B) (Hanesch et al, 1989;Omoto et al, 2018). We recorded calcium activity in the dendrites of two populations of ring neurons in the bulb, one innervating the medial two-thirds of the BUs (R2; R19C08-Gal4) and one innervating the BUa (R4m; R34H10-Gal4) (Fig.…”
Section: R4m Ring Neurons Receive Polarization-tuned Responses From Tmentioning
confidence: 99%
“…In Drosophila, this tethering is thought to come from a large population of inhibitory ring neurons (Hanesch et al, 1989;Homberg et al, 2018;Lin et al, 2013;Omoto et al, 2018;Xie et al, 2017;Young and Armstrong, 2010). However, this has not yet been verified experimentally.…”
Section: Ring Neurons Tether the Compass To Visual Scenes By Selectivmentioning
confidence: 99%
“…A potential complication is that there are many types of ring neurons, only some of which are visually tuned (Homberg et al, 2011;Omoto et al, 2017;Omoto et al, 2018;Seelig and Jayaraman, 2013;Shiozaki and Kazama, 2017;Sun et al, 2017) To identify appropriate visual ring neurons to reconstruct in the EM dataset, we performed stochastic labeling of broad ring neuron lines using the FLP-out technique ( Figure S4A) (Golic and Lindquist, 1989) (see Methods). This technique allows for individual neurons to be tagged, and here we used it to express GCaMP6f in single neurons in order to monitor their Ca 2+ activity.…”
Section: Ring Neurons Tether the Compass To Visual Scenes By Selectivmentioning
confidence: 99%
“…We expressed this construct in Ring (R) neurons, GABAergic neurons that send sensory input to the central complex 20 . R neurons are divided into types based on morphology 21 , here we focused on the R2 type. We expressed SPARC2-D-CsChrimson::tdTomato in a subset of R2 neurons (Figures 2F-H”).…”
Section: Main Textmentioning
confidence: 99%